Analysing Mutual Surveillance Practices During Long-Term Kidnapping Situations: The Case of Jungle Kidnapping Camps in Colombia - Tamayo Gomez, Camilo (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
Kidnapping as a crime of (im)mobility can be understood as a social act of mutuality and reciprocity, where the interaction between kidnappers and kidnappees shapes a broader system of connected activities of surveillance, intimacy, control, and consent. This article argues that during situations of long-term kidnapping, novel forms of social interaction emerge as a result of mutual surveillance practices between surveillance agents (kidnappers) and surveillance objects (kidnappees). It focuses on analysing how members of The Revolutionary Armed Forces of Colombia (FARC) (the kidnappers) and Colombian politicians, police, and army personnel (the kidnappees) conducted mutual practices and activities of surveillance during their lengthy cohabitation inside jungle kidnapping camps. It presents the results of thirty-three semi-structured interviews with victims of long-term kidnapping in Colombia and eleven structured interviews with FARC ex-combatants who were involved in kidnapping operations. The article demonstrates that the senses of mutuality, reciprocity, and intimacy were crucial to creating an unconventional surveillance regime inside jungle kidnapping camps in Colombia.